Cardio-respiratory interactions in acute asthma - Caplan, Morgan; Hamzaoui, Olfa (Frontiers in Physiology, 2023)
Asthma encompasses of respiratory symptoms that occur intermittently and with varying intensity accompanied by reversible expiratory airflow limitation. In acute exacerbations, it can be life-threatening due to its impact on ventilatory mechanics. Moreover, asthma has significant effects on the cardiovascular system, primarily through heart-lung interaction-based mechanisms. Dynamic hyperinflation and increased work of breathing caused by a sharp drop in pleural pressure, can affect cardiac function and cardiac output through different mechanisms.